Hubungan Pengetahuan dengan Tindakan Personal Hygiene pada Santri yang Menderita Scabies di Pondok Pesantren Darul Arafah Deli Serdang - Panggabean, Dodi Ardiansyah; Andayani, Lita Sri (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2024)
Background. Scabies ranks third among the twelve types of skin diseases in Indonesia. It is commonly found in high-density living environments such as pesantrens (Islamic boarding schools). Scabies affects the morbidity rate and causes itching, which can impact the concentration of affected individuals during studying. Scabies is the third most frequently reported skin disease and is prevalent in the Darul Arafah Deli Serdang poskestren. Aim. To analyze the relationship between knowledge and personal hygiene practices among students suffering from scabies at Pondok Pesantren Darul Arafah Deli Serdang Method. This study is a quantitative research with an analytical observational design using a cross-sectional approach. The sampling technique used was simple random sampling. Data analysis was conducted using univariate and bivariate analyses. Result. The results of this study indicate a correlation between (internal factor) knowledge and personal hygiene practices, with a p-value of 0.048 < (α = 0.05). There is also a correlation between (external factor) sources of information and personal hygiene practices, with a p-value of 0.000 < (α = 0.05). Furthermore, there is a correlation between the role of the poskestren and personal hygiene practices, with a p-value of 0.026 < (α = 0.05)